2005
DOI: 10.1074/jbc.m413446200
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Metabolic Pathway for Degradation of 4-Nonylphenol Environmental Contaminants by Sphingomonas xenophaga Bayram

Abstract: Several nonylphenol isomers with ␣-quaternary carbon atoms serve as growth substrates for Sphingomonas xenophaga Bayram, whereas isomers containing hydrogen atoms at the ␣-carbon do not (Gabriel, F. L. P., Giger, W., Guenther, K., and Kohler, H. Furthermore, two metabolites originating from 4-n-nonylphenol were identified as 4-hydroxy-4-nonyl-cyclohexa-2,5-dienone and 4-hydroxy-4-nonyl-cyclohex-2-enone by high pressure liquid chromatography-mass spectrometry. We conclude that nonylphenols were initially hydrox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
89
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(95 citation statements)
references
References 32 publications
5
89
1
Order By: Relevance
“…The above results indicate that p-nonylphenol was metabolized by ipso-addition to nonylquinol by rat or human liver microsomal P450. This compound has been reported to be a metabolite of nonylphenol in bacteria, 11) but has not been reported to be a metabolite in humans or animals.…”
Section: Discussionmentioning
confidence: 98%
“…The above results indicate that p-nonylphenol was metabolized by ipso-addition to nonylquinol by rat or human liver microsomal P450. This compound has been reported to be a metabolite of nonylphenol in bacteria, 11) but has not been reported to be a metabolite in humans or animals.…”
Section: Discussionmentioning
confidence: 98%
“…It has been reported that NP could be degraded with fission of the phenol ring by some isolated strains, and it seems to be able to further degrade the aromatic moiety of NP isomers as growth substrates [30,31] proved the existence of a novel pathway that enables bacteria to detach the alkyl substituent of an NP isomer as C9 alcohol and to utilize the ring as a source of carbon and energy. As for NPEOs, it is reported that ultimate biodegradation of the metabolites occurs more slowly, if at all, because of the need for a specific enzyme or bacterial population [32].…”
Section: Variations Of Functional Genes During Npeo and Np Degradationmentioning
confidence: 99%
“…Although nonylphenol is recalcitrant in nature, its bioavailability has triggered extensive studies on its bio-remediation by use of some yeast and gram-negative bacteria. Candida aquaetexotoris was reported to decompose the alkyl chain of nonylphenol to give 4-acetylphenol (Vallini et al, 2001), while several bacteria such as Sphingomonas xenophaga (Gabriel et al, 2005), Sphingomonas cloacae (Fuji et al, 2000), and Sphingobium amiense (Ushiba et al, 2003) metabolized its aromatic moiety to the corresponding C9 alcohols.…”
Section: Introductionmentioning
confidence: 99%